Desain dan Pabrikasi Alat Ukur Suhu dan Kelembaban Berbasis Modul Mikrokontroler ATMega 16A-PU - Joko Santoso; Iwan Sugriwan; Arfan Eko Fahrudin; Tanto Budi Susilo; Oni Soesanto; Hisyam Musthafa; Alan Dwi Wibowo; Susi Susi (Lambung Mangkurat University Press, 2022)
Research on design and fabrication of temperature and humidity measuring devices based on the ATMega 16A-PU microcontroller module can be realized directly on the FFB heating system. Temperature and humidity measuring devices consist of DC power supply, voltage follower, SHT11 sensor module, LM35 Waterproof sensor, 20x4 character LCD and ATMega 16A-PU microcontroller module. Whereas the FFB heating system consists of steam, boiler, air control room, and chamber. The system can be realized by placing the LM35 Waterproof sensor inside the air control room and the SHT11 sensor module inside the chamber. This system is also equipped with data acquisition software using the Delphi 7.0 program to display measured data in real-time and save it to Excel and the database. Tests carried out by flowing using wet steam generated from the boiler into the air control room and chamber. The average error value of reading the standard gauge with a gauge that has been made for the LM35 Waterproof sensor with a measurement range of 20-90ºC is 1.22ºC. As for the SHT11 sensor module, the average error value of readings with a measurement range of 20-90ºC and 40-90% is 1.04°C and 4.04%